2017
DOI: 10.1017/s1751731117000088
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response and semen quality of rabbit bucks supplemented with Moringa leaves ethanolic extract during summer season

Abstract: Exposure of rabbit bucks to summer heat stress reduces their homeostasis and semen quality leading to a temporal subfertility. The potentiality of ethanolic extract of Moringa oleifera leaves (M. oleifera ethanolic extract (MLEE)) to reduce negative impacts of heat stress on physiological and semen quality traits was investigated. A total of 28 adult V-line rabbit bucks were randomly distributed among four experimental groups of seven rabbits each. The first group received water (placebo) and served as a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 28 publications
5
73
0
2
Order By: Relevance
“…These values are within the previously published data by (Singh et al, 2007) and Olugbemi et al, 2010) who found that Moringa oleifera leaves is an excellent source of protein (22-36%) and minerals. The chemical analysis values of SDMOL in the present study were in harmony with Makkar and Becker (1996) and El-Desoky et al (2017). In addition, Aye and Adegun (2013) found that percentages of DM of Moringa oleifera leaves meal(MOLM) to be 93.63±0.01, ash (7.96±0.03), CP (22.23±0.25), CF (6.77±0.01), EE (6.41±0.01), NFE (40.28+0.25) and gross energy was (14.790 MJ/kg).…”
Section: Proximate Analysis Of Sun Dried Moringa Oleifera Leaves and supporting
confidence: 81%
“…These values are within the previously published data by (Singh et al, 2007) and Olugbemi et al, 2010) who found that Moringa oleifera leaves is an excellent source of protein (22-36%) and minerals. The chemical analysis values of SDMOL in the present study were in harmony with Makkar and Becker (1996) and El-Desoky et al (2017). In addition, Aye and Adegun (2013) found that percentages of DM of Moringa oleifera leaves meal(MOLM) to be 93.63±0.01, ash (7.96±0.03), CP (22.23±0.25), CF (6.77±0.01), EE (6.41±0.01), NFE (40.28+0.25) and gross energy was (14.790 MJ/kg).…”
Section: Proximate Analysis Of Sun Dried Moringa Oleifera Leaves and supporting
confidence: 81%
“…The use of phytochemicals have been proven to improve and protect against poor semen parameters (Abarikwu et al ., ; El‐Desoky et al ., ), in this study, Naringenin proved potent enough to attenuate the HAART‐induced toxicities on the spermatozoa. Although the marked decrease in sperm count in the Naringenin only groups depict that Naringenin may only serve as a prophylaxis rather than a potentiator in male fertility.…”
Section: Discussionmentioning
confidence: 50%
“…They found that daily feed intake (g) increased with increasing Moringa peregrine seeds meal (g/Kg diet) compared with those in the control group. While, El-Desoky et al (2017) found that feed intake and BW of rabbit bucks supplemented with Moringa leaves ethanolic extract during summer season were not affected significantly by the treatment. Moreover, Ahmed (2017) found that final body weight, daily weight gain and relative growth rate were insignificantly increased with NZW rabbits fed MLM at the rate of 12.5 and 19%.…”
Section: Fattening Periodmentioning
confidence: 81%